Phenotypic Modifications in Staphylococcus aureus Cells Exposed to High Concentrations of Vancomycin and Teicoplanin - Gonçalves, Fábio D. A.; de Carvalho, Carla C. C. R. (Frontiers in Microbiology, 2016)
Bacterial cells are known to change the fatty acid composition of the phospholipids as a phenotypic response to environmental conditions and to the presence of toxic compounds such as antibiotics. In the present study, Staphylococcus aureus cells collected during the exponential growth phase were challenged with 50 and 100 mg/L of vancomycin and teicoplanin, which are concentrations high enough to kill the large majority of the cell population. Colony-forming unit counts showed biphasic killing kinetics, typical for persister cell enrichment, in both antibiotics and concentrations tested. However, fluorescence microscopy showed the existence of viable but non-culturable (VBNC) cells in a larger number than that of possible persister cells. The analysis of the fatty acid composition of the cells showed that, following antibiotic exposure up to 6 h, the survivor cells have an increased percentage of saturated fatty acids, a significant reduced percentage of branched fatty acids and an increased iso/anteiso branched fatty acid ratio when compared to cells exhibiting a regular phenotype. This should result in lower membrane fluidity. However, cells exposed for 8-24 h presented an increased branched/saturated and lower iso/anteiso branched fatty acid ratios, and thus increased membrane fluidity. Furthermore, the phenotypic changes were transmitted to daughter cells grown in drug-free media. The fact that VBNC cells presented nearly the same fatty acid composition as those obtained after cell growth in drug-free media, which could only be the result of growth of persister cells, suggest that VBNC and persister phenotypes share the same type of response to antibiotics at the lipid level.